Um paralelo sobre a aposentadoria por idade dos trabalhadores urbano e rural - Costa, Valeria de Fátima Izar Domingues da (2005)
ABSTRACT The goal of this current research work is to study retirement by age of urban and rural workers, comparing those who contribute to Social Security to the rural workers who do not pay any contribution. The choice for this subject was due to the finding that, in spite of the Constitution of 1988 specify, as principle, the equation between urban and rural workers, this fact, up to the current time, is not seen in practice. Then, this is the reason why this topic was selected to be studied, i.e., calling the attention to the disparity that is seen in our country nowadays. The central hypothesis of this research study is based on the supposition that the representative legislators intend to keep the dignity of the human being, giving benefits to the elderly, whether urban or rural workers, however it allows for a distinguished treatment between the insured urban and rural workers and between the elderly and the disabled ones, as it is shown on Laws: 8.213/91 and 10.666/03, being sometimes the same and sometimes not. As for the theoretical-methodological aspects, it is ruled, mainly, on the set of constitutional principles that establish the Brazilian Social Security. This research work is mainly a theoretical study, being the systematic method applied to the studied subject. As a result, it was concluded that there is an urgent need for modifying the legislation, classifying the rural workers who do not contribute to Social Security as an employee or occasional worker; giving the same treatment to the benefits by incapacity as the treatment that is given by Law 10.666/03 to other retirement types; enforcing the social security constitutional principles when providing benefits, in order to extinguish social disparity, respecting the dignity.